2015
DOI: 10.1261/rna.052456.115
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of Macpiwi1 in transposon silencing and stem cell maintenance in the flatworm Macrostomum lignano

Abstract: PIWI proteins and piRNA pathways are essential for transposon silencing and some aspects of gene regulation during animal germline development. In contrast to most animal species, some flatworms also express PIWIs and piRNAs in somatic stem cells, where they are required for tissue renewal and regeneration. Here, we have identified and characterized piRNAs and PIWI proteins in the emerging model flatworm Macrostomum lignano. We found that M. lignano encodes at least three PIWI proteins. One of these, Macpiwi1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…M. lignano also provides an interesting model for the study of germ cell biology, because neoblasts are able to differentiate into germ cells. As an example, we are already beginning to probe the roles of the piRNA pathway in transposon silencing and neoblast maintenance in M. lignano (70).…”
Section: Discussionmentioning
confidence: 99%
“…M. lignano also provides an interesting model for the study of germ cell biology, because neoblasts are able to differentiate into germ cells. As an example, we are already beginning to probe the roles of the piRNA pathway in transposon silencing and neoblast maintenance in M. lignano (70).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first genome and transcriptome assemblies were published (Wasik et al, 2015), and transgenesis utility was demonstrated (Marie-Orleach et al, 2014, 2016). Despite this available toolbox, the described molecular markers for proliferating cells in M. lignano are still limited to piwi and vasa , which are expressed in both somatic neoblasts and proliferating germline cells (Pfister et al, 2007, 2008; De Mulder et al, 2009; Zhou et al, 2015). Consequently, there is an urgent need to identify more useful neoblast markers to develop this animal as a model for in vivo stem cell biology.
10.7554/eLife.20607.002Figure 1. Macrostomum lignano as model organism and experimental set up.( A ) Schematic representation, bright field image, and confocal projection of BrdU and phospho-histone H3 immunostaining (green: S-phase cells, red: mitotic cells) of an adult M. lignano .
…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that PIWIs can regulate non-transposable targets (Goh et al, 2015;Kiuchi et al, 2014;Rajasethupathy et al, 2012;Rouhana et al, 2014;Saito et al, 2009;Zhang et al, 2015). In addition, recent studies investigating flatworm PIWIs suggest that PIWIs might play another important function in the maintenance of PSCs (Rouhana et al, 2014;Zhou et al, 2015). In fact, histone h4 was identified as a posttranscriptional target of a cytoplasmic PIWI in neoblasts in the planarian S. mediterranea (Rouhana et al, 2014).…”
Section: Planarian Nuclear Piwi and Pirnas Regulate The Expression mentioning
confidence: 99%
“…Recently, the expression of piwi family genes in adult multi‐/pluripotent stem cells was reported in some invertebrates (Funayama, Nakatsukasa, Mohri, Masuda, & Agata, ; Juliano et al., ; Palakodeti, Smielewska, Lu, Yeo, & Graveley, ; Reddien, Oviedo, Jennings, Jenkin, & Sánchez Alvarado, ; Zhou et al., ). One of these invertebrates, the freshwater planarian, is known to possess PSCs (neoblasts) throughout its adult body, which enables it to regenerate its entire body from tiny fragments by rapidly supplying differentiated cells in response to positional information, and to maintain tissue homeostasis (Agata, Tasaki, Nakajima, & Umesono, ; Agata & Watanabe, ; Shibata, Rouhana, & Agata, ; Umesono et al., ; Wagner, Wang, & Reddien, ).…”
Section: Introductionmentioning
confidence: 99%